SISTEM AKUNTANSI PENGGAJIAN PADA PT MANGKUJENANG HARMONI SINERGY DI SAMARINDA - Ivana Nina Esterlin Barus3, Fendy Dwi Julian 1 Eddy Soegiarto K 2 (EKONOMIA, 2020)
The formulation of the research problem is whether the employee payroll accounting system is in accordance with the elements of internal control. The purpose of this study is to examine the suistability of the employee payroll accounting system with elements of internal control at PT. Mangkujenang Harmony Sinergy.The research hypothesis is the employee payroll accounting system at PT. Mangkujenang Harmoni Sinergy is not in accordance with the elements of internal control.The research was conducted by field research, namely data collection by examining the field directly with interviews, using questionnaire techniques with questions that have been determined to employees of PT. Mangkujenang Harmony Sinergy. The conclusion that the employee payroll accounting system carried out by PT. Mangkujenang Harmoni Sinergy is in accordance with the elements of internal control. then the hypothesis is rejected.